# Solve for x (x+18)/-4=8

x+18-4=8
Multiply both sides of the equation by -4.
-4⋅x+18-4=-4⋅8
Simplify both sides of the equation.
Simplify -4⋅x+18-4.
Cancel the common factor of 4.
Factor 4 out of -4.
4(-1)⋅x+18-4=-4⋅8
Factor 4 out of -4.
4⋅-1⋅x+184⋅-1=-4⋅8
Cancel the common factor.
4⋅-1⋅x+184⋅-1=-4⋅8
Rewrite the expression.
-1⋅x+18-1=-4⋅8
-1⋅x+18-1=-4⋅8
Simplify the expression.
Move the negative one from the denominator of x+18-1.
-1⋅(-1⋅(x+18))=-4⋅8
Rewrite -1⋅(x+18) as -(x+18).
-1⋅(-(x+18))=-4⋅8
-1⋅(-(x+18))=-4⋅8
Apply the distributive property.
-1⋅(-x-1⋅18)=-4⋅8
Multiply -1 by 18.
-1⋅(-x-18)=-4⋅8
Apply the distributive property.
-1(-x)-1⋅-18=-4⋅8
Multiply -1(-x).
Multiply -1 by -1.
1x-1⋅-18=-4⋅8
Multiply x by 1.
x-1⋅-18=-4⋅8
x-1⋅-18=-4⋅8
Multiply -1 by -18.
x+18=-4⋅8
x+18=-4⋅8
Multiply -4 by 8.
x+18=-32
x+18=-32
Move all terms not containing x to the right side of the equation.
Subtract 18 from both sides of the equation.
x=-32-18
Subtract 18 from -32.
x=-50
x=-50
Solve for x (x+18)/-4=8